Identification of Residues in the BST-2 TM Domain Important for Antagonism by HIV-1 Vpu Using a Gain-of-Function Approach - Yoshida, Takeshi; Kao, Sandra; Strebel, Klaus (Frontiers in Microbiology, 2011)
The HIV-1 Vpu protein enhances the release of viral particles from the cell surface in a cell-type specific manner. In the absence of Vpu, nascent virions remain tethered to the cell surface in restricted cell types. Recently, the human host factor BST-2/CD317/tetherin was found to be responsible for the inhibition of virus release. It was also reported that HIV-1 Vpu can target human BST-2 but is unable to interfere with the function of murine or simian BST-2. We performed a gain-of-function study to determine which of the differences between human and rhesus BST-2 account for the differential sensitivity to Vpu. We transferred human BST-2 sequences into rhesus BST-2 and assessed the resulting chimeras for inhibition of HIV-1 virus release and sensitivity to Vpu. We found that rhesus BST-2 carrying the transmembrane (TM) domain of human BST-2 is susceptible to HIV-1 Vpu. Finally, a single-amino-acid change in the rhesus BST-2 TM domain was sufficient to confer Vpu sensitivity.